Identifying sex similarities and differences in structure and function of the sinoatrial node in the mouse heart - Yin, Zeyuan; Torre, Eleonora; Marrot, Manon; Peters, Colin H.; Feather, Amy; Nichols, William G.; Logantha, Sunil Jit R. J.; Arshad, Areej; Martis, Simran Agnes; Ozturk, Nilay Tugba; Chen, Weixuan; Liu, Jiaxuan; et al. (Frontiers in Medicine, 2024)
The sinoatrial node (SN) generates the heart rate (HR). Its spontaneous activity is regulated by a complex interplay between the modulation by the autonomic nervous system (ANS) and intrinsic factors including. This study aimed to elucidate the sex-specific differences in heart morphology and SN function, focusing on basal HR, expression and function of hyperpolarization-activated HCN4 and HCN1 channels and other players contributing to diastolic depolarization and spontaneous action potentials (APs). Body weight, heart weight and tibia length of young adult male and female mice were measured. Conscious and unconscious in-vivo HR was recorded as well as stroke volume and ejection fraction. Ex-vivo HR was measured via Langendorff apparatus. Volume of hearts were measured from ex-vivo hearts by microcomputed tomography. Immunohistochemistry targeting HCN4 and HCN1 was conducted. The funny current (If) of SN cells in 1 nM and following wash-on of 1 μM isoproterenol (ISO) were recorded via whole cell patch clamp. The APs of SN tissue were recorded via sharp microelectrode and optical mapping of membrane voltage. The relative abundance of mRNAs was measured by qPCR. Heart weight to tibia length ratio and heart volume of females were significantly smaller than males. Unconscious in-vivo HR in male mice was higher than that in females. HCN4 and HCN1 expression in the SN in both male and females was similar. Wash-on 1 μM ISO in the same cells induced a significantly increased shift of V0.5 to more positive voltages in males than in females. The expression of receptors Adrb1 and chrm2 at mRNA level in male was higher compared with that in female SN. Early diastolic depolarization rate in APs from peripheral SN were higher in male mice. Frequency of SN APs and spatial localization of the leading site in control were similar for both sexes, and similar significant response to ISO 100 nM superfusion. Males display faster in-vivo HR associated with increased expression of Adrb1 in male SN. This suggests a possible difference in the β-adrenergic modulation in males and females. Further investigations are necessary to pinpoint the precise molecular substrates responsible for these differences.